Socialization of the Healthy Elderly Program at Posbindu RW 14 Ciwalen Village Garut City District - Udin Rosidin; Nina Sumarni; Dadang Purnama; Iwan Shalahuddin; Witdiawati Witdiawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
ABSTRACT Current developments in science and technology have a positive impact on increasing average life expectancy. This condition has resulted in an increase in the proportion of the population from adults to the elderly. The increase in population in this age group has good potential, although there are still many adults and elderly people who experience negative impacts from this development. These negative impacts include the increase in the adult and elderly population experiencing non-communicable diseases. This is in line with the increasing risk factors for non-communicable diseases. One strategy for controlling risk factors for non-communicable diseases that is efficient and effective is the promotion of healthy elderly programs. The aim of this activity is to increase the knowledge of the adult and elderly community in implementing healthy living behavior as a preventive effort in controlling risk factors for non-communicable diseases. The activity stages start from social preparation and administrative preparation. Then it continues with the implementation and evaluation stages of activities. The results of the activity showed an increase in public knowledge in controlling risk factors for non-communicable diseases by 18.7 points. The average pretest score was 64.3 points and the average posttest score was 83 points. Activities ran smoothly according to the planned time. It is hoped that the socialization activities for the healthy elderly program that have been implemented can be continued periodically by the Guntur Community Health Center and Ciwalen Village.